The light: science and applications - Velonakis, Ioannis N. (Open Schools Journal for Open Science, 2021)
“The light: science and application” is a project originally applied to fourteen to sixteen-year-old students of Laimos Junior and Senior High School the Municipality of Prespes, in the North Western Greece, although it was originally designed for slightly older students. The project aims to increase students’ motivation and interest in science by renewing the corresponding educational material, implementing modern teaching methods and bringing them into contact with the work of university scientific laboratories. The project is based on the collaboration among schools, universities and scientific laboratories. It encourages the use of new teaching methods and applications in the classroom and the contextualization of STEM learning.